Pendidikan Karakter pada Sistem Boarding School - Agus Triyono (Institut Agama Islam Negeri Purwokerto, 2019)
The times are increasingly rapid, marked by advances in science and technology, whether they realize it or not have a sharp enough impact on society, including adolescents and school-age children. The positive impact arising from the development of science and technology is a great hope for all levels of society. On the other hand, the emergence of negative impacts is something that cannot be denied and has recently occurred in society, including in the world of education. Bullying cases, student fights, skipping school, actions against teachers are becoming more frequent. This makes parents, practitioners, administrators and observers of education quite concerned and stimulated to create and emphasize education that is able to produce students who have strong character, have akhlaqul karimah. Realizing that this condition is also the government's responsibility, the government determines the importance of character education in educational institutions as stipulated in Presidential Regulation No. 78 of 2017 concerning Strengthening Character Education. One of the efforts taken by education providers is to provide education with boarding services, namely educational services by requiring students to live in school dormitories, with the aim that the education process can run twenty-four hours, with full attention and monitoring and guidance from the boarding supervisor. With this boarding system, schools will find it easier to condition students to participate in activities organized by schools including religious education as the core of character education in theory and practice directly with the guidance of teachers in dormitories. The boarding system education also isolates students from socializing in a wide environment that has recently been exposed to many negative influences from the internet, social media and so on. In boarding schools students are taught to have a strong character through a maximum educational process. Abstrak Perkembangan zaman yang semakin pesat yang ditandai dengan kemajuan ilmu pengetahuan dan teknologi disadari atau tidak memberikan dampak yang cukup tajam di masyarakat termasuk kalangan remaja dan anak-anak usia sekolah. Dampak positif yang muncul dari perkembangan iptek menjadi harapan besar seluruh lapisan masyarakat. Di sisi lain munculnya dampak negatif merupakan hal yang tidak dapat dipungkiri lagi dan akhir-akhir ini terjadi di masyarakat termasuk pada dunia pendidikan. Kasus bullying, perkelahian pelajar, membolos sekolah, tindakan melawan guru, semakin sering terjadi. Hal ini membuat kalangan orang tua, praktisi, penyelenggara dan pemerhati pendidikan cukup prihatin dan terstimulasi untuk menciptakan dan menekankan kepada pendidikan yang mampu menghasilkan peserta didik yang mempunyai karakter kuat, mempunyai akhlaqul karimah. Menyadari kondisi ini juga merupakan tangggung jawab pemerintah, maka pemerintah menetapkan tentang pentingnya pendidikan karakter pada lembaga pendidikan yang tertuang pada Peraturan Presiden no 78 Tahun 2017 Tentang Penguatan Pendidikan Karakter. Salah satu upaya yang ditempuh oleh penyelenggara pendidikan adalah dengan menyelenggarakan pendidikan dengan layanan boarding yaitu layanan pendidikan dengan mewajibkan peserta didik untuk tinggal di asrama sekolah, dengan tujuan proses pendidikan bisa berjalan dua puluh empat jam, dengan perhatian dan pemantauan serta bimbingan penuh dari pembimbing asrama. Dengan sistem boarding ini sekolah akan lebih mudah untuk mengkondisikan peserta didik untuk mengikuti kegiatan-kegiatan yang diselenggarakan oleh sekolah termasuk dalam pendidikan keagamaan sebagai inti dari pendidikan karakter secara teori maupun praktik langsung dengan bimbingan guru di asrama. Pendidikan sistem boarding juga mengisolasi peserta didik dari pergaulan di lingkungan luas yang akhir-akhir ini banyak terpapar pengaruh negatif dari internet, media sosial dan sebagainya. Di sekolah boarding peserta didik diajari untuk memiliki karakter kuat melalui proses pendidikan yang maksimal.